Fluoxetine rescues impaired hippocampal neurogenesis in a transgenic A53T synuclein mouse model. - Kohl, Zacharias; Winner, Beate; Ubhi, Kiren; Rockenstein, Edward; Mante, Michael; Muench, Martina; Barlow, Carolee; Carter, Todd; Masliah, Eliezer; Winkler, Jürgen (European Journal of Neuroscience, 2012)
The accumulation of alpha-synuclein in Lewy bodies and Lewy neurites of different neuronal populations is one of the neuropathological hallmarks in Parkinson disease (PD). Overexpression of human wildtype or mutant alpha-synuclein affects the generation of new neurons in the adult dentate gyrus (DG) of the hippocampus in models of PD. Hippocampal dysfunction with reduced neurogenesis plays an important role in the pathogenesis of depression, an important non-motor symptom in PD. Moreover, effective antidepressant treatment is still an unmet need in PD. The present study explored if impaired hippocampal neurogenesis in the A53T transgenic animal model of PD may be restored by chronic oral application of the selective serotonin reuptake inhibitor (SSRI) fluoxetine. First, we determined the expression pattern of transgenic mutant A53T synuclein in developing DG neurons and showed early expression of the transgene linked to a severely impaired neurogenesis. After chronic fluoxetine treatment we observed an increased adult neurogenesis in the hippocampus of more than threefold in treated A53T mice compared with controls. The pro-neurogenic effect of chronic fluoxetine application is predominantly related to an increased proliferation of neural precursor cells in the DG, and to a lesser extent by induction of differentiation into mature neurons. Analysis of the underlying mechanisms revealed an induction of brain-derived and glial cell-derived neurotrophic factor levels as a result of fluoxetine treatment. This study underlines the large potential of SSRI-dependent mechanisms to stimulate adult hippocampal neurogenesis in alpha-synuclein models and may lead to novel means to improve neuropsychiatric symptoms in PD.
EVALuna2:25298